Laparoendoscopic single-site and natural orifice transluminal endoscopic surgery in urology: a critical analysis of the literature - Autorino, R (2011)
CONTEXT: Natural orifice transluminal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS) have been developed to benefit patients by enabling surgeons to perform scarless surgery. OBJECTIVE: To summarize and critically analyze the available evidence on the current status and future perspectives of LESS and NOTES in urology. EVIDENCE ACQUISITION: A comprehensive electronic literature search was conducted in June 2010 using the Medline database to identify all publications relating to NOTES and LESS in urology. EVIDENCE SYNTHESIS: In urology, NOTES has been completed experimentally via transgastric, transvaginal, transcolonic, and transvesical routes. Initial clinical experience has shown that NOTES urologic surgery using currently available instruments is indeed possible. Nevertheless, because of the immaturity of the instrumentation, early cases have demanded high technical virtuosity. LESS can safely and effectively be performed in a variety of urologic settings. As clinical experience increases, expanding indications are expected to be documented and the efficacy of the procedure to improve. So far, the quality of evidence of all available studies remains low, mostly being small case series or case-control studies from selected centers. Thus, the only objective benefit of LESS remains the improved cosmetic outcome. Prospective, randomized studies are largely awaited to determine which LESS procedures will be established and which are unlikely to stand the test of time. Technology advances hold promise to minimize the challenging technical nature of scarless surgery. In this respect, robotics is likely to drive a major paradigm shift in the development of LESS and NOTES. CONCLUSIONS: NOTES is still an investigational approach in urology. LESS has proven to be immediately applicable in the clinical field, being safe and feasible in the hands of experienced laparoscopic surgeons. Development of instrumentation and application of robotic technology are expected to define the actual role of these techniques in minimally invasive urologic surgery.